Scanning electron microscopy and voltammetry of preferentially oriented polycrystalline platinum surfaces - Cerviño, R. M. (1985)
Scanning electron micrographs are taken for a polycrystalline platinum wire before and after the application of a repetitive potential scan at more than 10,000 V/s. The change of the surface structure observed is related to a specific hydrogen adatom voltammogram usually obtained for single crystal surfaces.